MENYOAL INDEPENDENSI DAN PROFESIONALITAS KOMISI PEMILIHAN UMUM DAERAH DALAM PENYELENGGARAAN PEMILU KEPALA DAERAH - Winardi, Winardi (Jurnal Konstitusi, 2010)
Elections of local heads are often characterized by anomalies in the local democratic practices. One of its triggers for the anomalies is dealing with independence and professionalism of the Komisi Pemilihan Umum Daerah (Local General Election Commission). In order to hold a honest and fair general election, a high and serious commitment is needed, though the commission under the version of the 22 law in the year of 2007 on the Implementation of General Election has a stronger and more independent position than the previous commission.